Development of Web-Based Media Google Sites on Learning IPS Material Me and My Needs in Class IV SD - Evita Pasha Andriani; Akhmad Junaedi (STKIP Taman Siswa Bima, 2025)
Web-based learning media ran Google Sites is still rarely used in social studies learning, which can result in decreased student learning outcomes. This study aims to develop and test the feasibility and effectiveness of Google Sites web-based learning media as a learning medium in my material and my needs for grade IV students of SDN 1 Winongsari. This research uses the Research and Development (R&D) method with the ADDIE model which consists of five stages of analysis, design, development, implementation, and evaluation. The research subjects involved lecturers, teachers, and grade IV students, with data collected through response questionnaires to assess content validity, language, implementation, visual appearance, and ease of use. The results showed that Google Sites is